The Degree of Use of Digital Content Design Applications by College of Humanities Students in the Distance Learning and Teaching Strategies Course - Alenazi, Nouf Farhan; Al-Mashouq, Nada AbdulAziz; Al-Bisher, Mona Abdullah (Journal of Curriculum and Teaching Methodology, 2025)
This Research aimed to identify the extent to which students of the College of Humanities at Northern Border University use digital content design applications in the course Teaching and Learning Strategies for Distance Education, and to examine their impact on learning motivation, in addition to highlighting major obstacles. The study employed a descriptive-analytical method and an electronic questionnaire covering three dimensions (usage, obstacles, and impact on motivation), applied to a random sample of 41 students. Findings indicated a moderate level of usage (3.13 out of 5), mainly for assignments and presentations (3.29). The main obstacles were time consumption (3.20), difficulty balancing tools with course requirements (3.05), and lack of training, with an overall mean (2.85). Results also revealed a clear positive impact on learning motivation (3.76), as 73.2% of students agreed that these applications enhanced creative expression 3.88, while 70.7% reported a sense of achievement (3.76). Significant differences in obstacles were found based on study level and prior digital course experience, but not gender. The Research recommended integrating specialized digital content design courses into humanities programs, organizing hands-on workshops (Canva, Book Creator, Genially), encouraging faculty to incorporate these tools, and enhancing technical infrastructure to reduce challenges.
Keywords: College of Humanities; digital content; design applications; teaching strategies; distance learning